2017
DOI: 10.1051/0004-6361/201525655
|View full text |Cite
|
Sign up to set email alerts
|

Rosette nebula globules: Seahorse giving birth to a star

Abstract: Context. The Rosette nebula is an H ii region ionized mainly by the stellar cluster NGC 2244. Elephant trunks, globules, and globulettes are seen at the interface where the H ii region and the surrounding molecular shell meet. Aims. We have observed a field in the northwestern part of the Rosette nebula where we study the small globules protruding from the shell. Our aim is to measure their properties and study their star-formation history in continuation of our earlier study of the features of the region. Met… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Elephant trunk and cometary structures are seen in the molecular clouds within the Sh2-282 H II region. These morphologies are frequently found in H II regions (Gahm et al 2006;Mäkelä et al 2017), and are predicted by the radiation driven implosion (RDI) simulations (Bertoldi 1989;Bisbas et al 2011). As shown in the 12 CO and 13 CO emission maps (Figure 3), the stellar winds and radiation from the massive stars in the BFS54 and Sh2-280 H II regions have apparently destroyed molecular clouds within the central parts of these H II regions and have excavated a circle-like (BFS54) or semicircle-like (Sh2-280) cavity, similar to the S287 (Gong et al 2016) and the N4 (Chen et al 2017) regions.…”
Section: Overall Distribution Of Molecular Clouds In the Regionmentioning
confidence: 93%
“…Elephant trunk and cometary structures are seen in the molecular clouds within the Sh2-282 H II region. These morphologies are frequently found in H II regions (Gahm et al 2006;Mäkelä et al 2017), and are predicted by the radiation driven implosion (RDI) simulations (Bertoldi 1989;Bisbas et al 2011). As shown in the 12 CO and 13 CO emission maps (Figure 3), the stellar winds and radiation from the massive stars in the BFS54 and Sh2-280 H II regions have apparently destroyed molecular clouds within the central parts of these H II regions and have excavated a circle-like (BFS54) or semicircle-like (Sh2-280) cavity, similar to the S287 (Gong et al 2016) and the N4 (Chen et al 2017) regions.…”
Section: Overall Distribution Of Molecular Clouds In the Regionmentioning
confidence: 93%
“…Molecular line observations in the CO lines, which directly measure the gaseous mass and kinematics, have been also obtained in several ETs (Sherwood & Dachs 1976;Schneps et al 1980;Gonzalez-Alfonso & Cernicharo1994;Massi et al 1997;Gahm et al 2006Gahm et al , 2013Haikala et al 2017Mäkelä et al 2017. As to the ETs in M16, several CO-line observations have been obtained (Pound 1998;White et al 1999;Andersen et al 2004;Schuller et al 2006;Pattle et al 2018;Xu et al 2019).…”
Section: Introductionmentioning
confidence: 96%
“…A number of observations of ETs have been obtained from infrared to X rays, particularly extensively in the far infrared (FIR), in the decades (Hester et al 1996;Pilbratt et al 1998;McCaughrean & Andersen 2002;Carlqvist, et al 2002;Urquhart et al 2003;Sugitani et al 2007;Linsky et al 2007Chaughan et al 2012Getman et al 2012;Hill et al 2012;Schneider et al 2016;Mäkelä et al 2017;Pattle et al 2018;Panwar et al 2019 ). See Oliveira (2008) for review on the ETs in M16 and star formation.…”
Section: Introductionmentioning
confidence: 99%
“…Elephant trunks (ET) provide us with unique tool to probe the interstellar physics of shock-accelerated molecular clouds at the interface with expanding HII regions as close-up views of triggered star forming (SF) fronts (Frieman 1954;Spitzer 1954;Osterbrock 1957). There have been a number of optical and infrared observations of ETs associated with galactic HII regions (Pottasch 1956;Hester et al 1996;Sugitani et al 2001Sugitani et al , 2007Carlqvist, Gahm, & Kristen 2002;Chaughan et al 2012;Getman et al 2012;Schneider et al 2016;Mäkelä et al 2017;Pattle et al 2018;Panwar et al 2018; and the literature therein), where heavy extinction has indicated that the ETs are dense molecular clouds.…”
Section: Introductionmentioning
confidence: 99%
“…However, only a limited number of molecular line observations have been obtained, which directly measure the physical properties of ETs such as the gaseous mass and kinematics ( Sherwood & Dachs 1976;Schneps et al 1980;Gonzalez-Alfonso & Cernicharo1994;Massi et al 1997;Pound 1998;White et al 1999;Gahm et al 2006Gahm et al , 2013Haikala et al 2017;Mäkelä et al 2017;Xu et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%